Comparison of Metacognition Awareness of Mathematics and Mathematics Education Students Based on the Ability of Mathematics - La Misu; I Ketut Budayasa; Agung Lukito; Rosdiana Rosdiana (SAINTIS Publishing, 2019)
Awareness of metacognition is one of mental process that occurs when a person knows what he thinks, including the knowledge and awareness to do something or realize the reason that. The purpose of this study is (1) to describe how the metacognition awareness of mathematics student and mathematics education student based on mathematical ability, and (2) to know the difference metacognitive awareness between of mathematics students with math education students based on mathematical ability. This research subject are the Department of Mathematics and Mathematics Education students of Halu Oleo University Kendari, Indonesia. This research is ex post facto by the data analysis using descriptive and inferential approach. Descriptive approach used to describe the level of metacognitive awareness of mathematics students and mathematics education students based on his mathematical abilities, whereas inferential approach used to see the difference in metacognition awareness of mathematics students and mathematics education students based math skills. The results of this study are: (1) the level of students metacognition awareness of Mathematics Department, generally located on level strategic use and level reflective use, while the level of students metacognition awareness of Education Mathematics Department, generally located on level aware use; (2) there is a significant difference between the awareness metacognition of math students with mathematics education student based on his mathematical abilities, and awareness metacognition of math student better than mathematics education students.